Mapa miasta jako konstrukt pamięci. Na przykładzie pamięci o Powstaniu Warszawskim we współczesnej Warszawie - Kurz, Iwona (Er(r)go. Teoria - Literatura - Kultura, 2006)
Iwona Kurz City Map as a Memory Construct. Remembering Warsaw Uprising in Contemporary Warsaw Contemplating the social and historical significance of the Warsaw Uprising and its 60th anniversary, the article points to a silent ever-presence of the event's painful reminders in the city's contemporary landscape, which — though seemingly erased from the map of everyday trivia and the city's obsessive mobility — still appear and re-appear in the background of every-day actions and as such constitute the historical unconscious of the celebrated 2003 Warsaw movie. The key point of the article revolves around the anniversary's celebrations, which, due to their scale and sophistication, rearranged the ordinary space of Warsaw turning it, through repetition and experience, into a space of "bleeding memory." This particular balance between dramatic past and its contemporary re-enactment not only introduces what Marianne Hirsch calls "post-memory," but also, if not in the first place, it provides one of the crucial cornerstones of national identity.